Retrospective Study of Blood Transfusion Transmitted Infections (HIV, HCV, HBV, Syphilis & Malaria] among the Blood Donors in Dhiraj Hospital (Medico Legal Update, 2021)
A blood transfusion is a way of adding blood to your body after an illness or injury. It’s a kind of life savingprocedure. But this procedure also has life threatening hazards. Transfusion transmitted infections are one ofthe major side effects of blood transfusion. We can prevent them by proper screening of blood products andpublic awareness. To know about trend of transfusion transmitted infections (TTI) for the blood donors ofDhiraj hospital blood bank, the study was done.Method: Study was done including blood donors of age 18-65 years from 2011 to 2016 retrospectively.TTIs testing for HIV, HBV and HCV was done with 3rd generation ELISA but from the year 2016 onwards4th generation ELISA was used for HIV testing. Syphilis and malaria screening was done with rapid cardtest.Result: Over a six year period total blood donation was 20,392. The overall prevalence of HIV, HbsAg,HCV, syphilis and malaria were 0.16%, 1.43%, 0.10%, 0.61% and 0.009% respectively.Conclusion: Nucleic acid amplification testing (NAT) must be applied that identify positive blood donorduring the immunological window period before seroconversion. Information to TTIs reactive donor is abest method to prevent the chance of repeated reactive donation.